POLA HUBUNGAN PANJANG BERAT IKAN NILA YANG DI BUDIDAYAKAN DI GERUNG NUSA TENGGARA BARAT - Septiana Dwiyanti Septiana; Muhammad Naufal Hawari; Muhammad Kholid Al Fauzan (Jurnal Intek Akuakultur, 2026)
An important aspect in tilapia cultivation is observing the relationship between the length and weight of the fish, which is an indicator of the fish's growth. One of the areas in West Nusa Tenggara that has great potential in tilapia cultivation is Gerung which is located in West Lombok Regency. The purpose of this study is to determine the growth pattern of tilapia in the region to help farmers adjust feed management, stocking density and maintenance systems to increase production. The method used is the survey method and regression analysis. The number of samples used in this study were 16 tilapia (Oreochromis niloticus) taken randomly from tilapia rearing ponds in Gerung District, West Lombok Regency. The average weight obtained in this study ranged from 169-400 grams with an average of 285 grams and a length of 25-39 cm, while the results of statistical regression of the relationship between the length and weight of tilapia, the regression equation obtained a value of Log Y = 25.419X 0.7394 with a correlation value (R2) of 43% and a value of b = 0.73, so that b <3 which means negative allometric where the condition of the fish experiences faster growth in length than weight gain